Sheep productivity in the Ethiopian highlands on a diet supplemented with urea-molasses block and/or noug cake - Kabaija, E.; Akalework, N.; Leng, R.A. (Springer, 1989)
A feeding experiment was carried out in which adult ewes of the Ethiopian Highland Menz breed grazed on meadow pasture were supplemented with urea-molasses block and/or Noug cake. There was low consumption of urea-molasses block (67g/d) and its contribution to total nitrogen requirements was minimal. Dietary treatment had no significant effect on live weight changes of ewes, their reproductive performance and performance of the lambs. When there was liver fluke infection, ewes and their lambs which were supplemented with urea-molasses block and/or Noug cake had better survival compared to those which did not get any supplements (35% mortality vs 55%). The rumen ammonia-N concentration was significantly lower in the control sheep (11 mg/100ml) and those that received only urea-molasses (14mg/100ml) and highest in sheep receiving the urea-molasses block and Noug cake (26mg/100 ml). The volatile fatty acid proportions were not significantly affected by the diets. Low level of urea-molasses block consumption seemed to be the main factor limiting the usefulness of the urea-molasses block and it is recommended that factors likely to enhance its consumption be investigated.